The Heroine’s Journey towards Wholeness as seen in Margaret Atwood’s Surfacing - Hendarti Azizah Ayuningtyas; Rahmawan Jatmiko (Lexicon, 2020)
This study discusses the psychological journey of the female heroine in Margaret Atwood's Surfacing. This paper applies the psychological approach since it is believed to be the most suitable approach to analyze the process of the heroine’s journey towards wholeness. It examines the process of individuation in the main plot of the novel and the characteristics of the process on the heroine’s personal quest. The portrayal of the individuation process is identified through the theory of individuation proposed by Charles Gustav Jung which discusses the process of the individual’s development towards psychological completeness. In order to support the analysis, library research was conducted using the novel as well as the supporting articles from any reliable websites. The result shows that the heroine’s journey can be translated as Jungian’s theory of individuation as there are six characteristics of the process of individuation found within the story. Furthermore, five stages occurred in the heroine’s journey, namely the recognition of the persona, the assimilation with the shadow, the confrontation with the animus, and lastly the appearance of the Self that leads the heroine towards psychological wholeness.